Dating through 210Pb - 137Cs implementation in Uruguay for the recognition of the climatic-environmental variability of the upper Holocene: Case study: Laguna de las Nutrias - Rocha - Uruguay (INNOTEC, 2020)
Geochronology constitutes a fundamental tool for the study of historical events. Its development in Uruguay has been closely linked with archaeological studies. In the last 20 years, dating techniques have expanded into other disciplines, leading to methodological changes and improvements. The most widely used method to study the chronology of most recent Holocene climatic and environmental events is 210Pb-137Cs. The objective of this manuscript is the development in Uruguay of the 210Pb-137Cs geochronological method and its application to a study case. For this, a vertical sediment core was taken from Laguna de las Nutrias (Rocha), which was sub-sampled, and the sections were measured by gamma spectrometry, determining the 210Pb, 226Ra and 137Cs radionuclides. The 210Pb concentration was mathematically modeled, finding that the best fit model is the constant rate of supply model. This model was positively corroborated against the historical profile of 137Cs activity from nuclear events. The annual sedimentation rate was calculated to be 3.1 ± 1.5 mm/year-1 from 1870 to 1986 AD and 4.7 ± 0.8 mm.year-1 after 1986 AD. Likewise, an extreme event possibly associated to the inherent climatic variability of Little Ice Age was inferred.
Keywords: Geochronology; sedimentation; paleolimnology